Earnings Management in Developing Countries: Iranian Listed Companies - Jamal Roudaki (Journal of Accounting, Business and Management (JABM), 2013)
This paper investigates earnings management exercises and motivations of Iranian listed companies and the level of corporate governance disclosure in these companies during 2008 and 2010 in the environment of no formal compulsory corporate governance regulations. Firm characteristics such as leverage, profitability, and company size are considered as dependent variables in relation to earnings management as dependent variable in an empirical analysis. Results indicate that listed companies manage their earnings both upward and downward, while upward earnings management is rocketed, downward managing decreases comparing 2008 and2010.Statistical relation between earnings management and firm characteristics are scattered over the period of the study. Earnings management exhibited a statistical significant relationship with leverage in 2010, ROA in 2009 and size in 2008. While voluntary corporate governance disclosure is so limited summing up the results reveals that five directors on the Board is common, in the most companies CEO is member of the Board but in very few firms CEO is chairman of directors' board. High concentrated Institutional ownership in the hands of state or semi government entities is dominated in the Iranian listed companies.